Towards understanding the hole making performance and chip formation mechanism of thermoplastic carbon fibre/polyetherketoneketone composite. (1st April 2022) - Ge, Jia; Catalanotti, Giuseppe; Falzon, Brian G.; McClelland, John; Higgins, Colm; Jin, Yan; Sun, Dan
Abstract: Here, we report the first study on the hole making performance of thermoplastic carbon fibre/polyetherketoneketone (CF/PEKK) composite. Different hole making methods (conventional drilling vs. helical milling) have been compared and the effect of different feed rates has been investigated. The effect of thermal-mechanical interaction on the resulting hole damage has been elucidated for the first time for carbon fibre reinforced thermoplastics (CFRTPs) hole making. In the material science dimension, advanced material characterization techniques have been deployed to reveal the material removal mechanisms at microscopic scale and unveil the underlying material structural change at a molecular level. Results show that the delamination damage of CF/PEKK is a result of the thermal-mechanical interaction. For conventional drilling, the high machining temperature (at low feed rate <0.1 mm/rev) has a stronger influence on the delamination damage and the delamination starts to show stronger dependence on the thrust force at high feed rate >0.1 mm/rev. In contrast, helical milling generates a much higher machining temperature which plays a more predominant role in the associated delamination damage. Microstructural analysis shows that all the hole surfaces feature matrix smearing, as a result of combined in-plane shear stress and high machining temperature. Conventional drilling leads to more severe hole wall microstructural damage (matrix loss and surface cavity) as compared to helical milling. Finally, thermal analysis reveals that the hole making process has led to significantly increased crystallinity in the PEKK matrix as a result of the strain-induced crystallization under the combined effect of shear stress and high temperature. Graphical abstract: Image 1 Highlights: Hole making performance of CF/PEKK is investigated for the first time. A comparative study on conventional drilling and helical milling is reported. The role of thermo-mechanical interaction is elucidated for CF/PEKK hole making. Chip morphology and the associated material removal mechanism are revealed. Shear-induced crystallization caused by hole making is reported for the first time.